DSM-5 Personality Disorders and Traits in Patients With Severe Health Anxiety. Issue 2 (February 2020) - Skjernov, Mathias; Bach, Bo; Fink, Per; Fallon, Brian; Soegaard, Ulf; Simonsen, Erik
Abstract : Abstract: Severe health anxiety (SHA)/hypochondriasis (HY) is often associated with personality pathology; however, studies report inconsistent results. In general populations, 12% have a personality disorder (PD). We assessed physician-referred psychiatric outpatients with SHA enrolled for a treatment study ( n = 84) with the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, 4th Edition ( DSM-IV ) axis II (SCID-II), Personality Inventory for DSM-5 (PID-5), Whiteley Index 7, and Short Health Anxiety Inventory, and the healthy controls ( n = 84) with PID-5 only. There were 71.4% of the patients who met criteria for PDs: avoidant (22.6%), obsessive-compulsive (16.7%), depressive (16.7%), dependent (7.1%), paranoid (3.6%), borderline (2.4%), and not otherwise specified (32.1%). Severity of personality pathology was associated with severity of health anxiety. In group comparisons, PID-5 trait domains of negative affectivity, detachment, low antagonism, and low disinhibition, and facets of anxiousness, separation insecurity, and low attention seeking emerged as unique predictors of SHA. Personality pathology is common among individuals with SHA/HY. Further research is needed to understand the nature of the relationship between health anxiety and personality pathology and to determine whether treatments that target both SHA/HY and personality pathology will improve short- and long-term outcomes.